Regarding gender relations: Gender identity or gender interaction styles? - Bazán Ramírez, Aldo (1996)
This study discusses sorne assumptions from the social determinism in the construction of gender roles, gender-typed identities, and gender relarions inequities. Ir is proposed that gender sryles of interaction are relatively invariant forms or dispositions related ro specific contexts of social interaction. Iris not enough ro say that socialization factors such as the family, school, mass media, and rhe inirial social group relations generare a typed gender identity or gender seggregation, but it is also necessary ro make explicit how preferences, beliefs and interaction sryles are structured according ro rhose factors and how these interactive tendencies are built u pon social interaction situations as part of a developmental process.